The Role of Arts and Ethics in the ‘Work in Progress’ Grade X Textbook through Content Analysis - Erika Grace Juliana Manurung; Yenni Erlita; Lia Lisyati; Lovita Christiani Napitupulu; Junus Situmorang; Samantha Yohana Situmorang (QISTINA: Jurnal Multidisiplin Indonesia, 2026)
The portrayal and function of the arts and moral principles in the Grade X English textbook Work in Progress are examined in this study. The study looks at the text, pictures, and educational activities in the textbook to determine how these components are presented using a qualitative content analysis method. The results demonstrate how the arts are mirrored in narratives, visuals, and culturally rich resources that foster students' involvement and creativity. In the meantime, ethical principles like cooperation, respect, and accountability are ingrained in discussions, texts, and assignments, assisting students in making connections between what they are learning and actual circumstances. These components not only enhance the educational process but also aid in the growth of students' critical thinking and character. In general, the incorporation of ethics and the arts contributes significantly to the textbook's increased relevance, meaning, and interactivity for students.